Public Expenditure Tracking and Service Delivery Survey : Education and Health in Honduras - Background Chapters - World Bank (World Bank, 2012)
This report aims at providing the Government of Honduras (GOH) with a tool to improve efficiency in the management of existing public resources in the education and health sectors, in order to increase access and provide better education and health services to the poor. Specifically, the objectives of the study are to: i) identify how resources are allocated and used in the education and health sectors; ii) identify leakages and inefficiencies in the system; iii) analyze how existing management models perform and how different public management instruments are applied in each sector; and iv) issue recommendations for improving the management of resources in the education and health sectors. The education and health sectors account for 46.2 percent of Central Government expenditures and have been highlighted as major drivers of growth. The main focus of the analysis in the education sector are the funds allocated to human resources given that it accounts for more than 80 per cent of the budget. The report presents the methodology and main findings from the survey that was carried out between November 2008 and October 2009. The main recommendation of the report is that an effort should be made in order to improve the scope, quality and transparency of the information collected on the provision of education and health services.